2002
DOI: 10.1128/aem.68.6.2838-2842.2002
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Vancomycin-Resistant Enterococci in Swedish Sewage

Abstract: In Europe the use of the growth promoter avoparcin is considered to have selected for vancomycin-resistant enterococci (VRE). Sweden ceased using avoparcin in 1986, and only occasional cases of VRE from hospitals have been reported since 1995. Within the framework of a European study, samples from urban raw sewage, treated sewage, surface water, and hospital sewage in Sweden (n ‫؍‬ 118) were screened for VRE. Surprisingly, VRE were isolated from 21 of 35 untreated sewage samples (60%), from 5 of 14 hospital se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
117
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 33 publications
6
117
1
8
Order By: Relevance
“…Bacterial resistance to antibiotic is a long-established, widely studied problem (6,8,19). Increasing attention has been directed recently to the responses of bacteria to biocides.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance to antibiotic is a long-established, widely studied problem (6,8,19). Increasing attention has been directed recently to the responses of bacteria to biocides.…”
Section: Introductionmentioning
confidence: 99%
“…Their role in such infections has increased due to their ability to acquire resistance to various antimicrobial agents, which renders them difficult to treat (Linden and Miller, 1999;Iversen et al, 2002;Kolar et al, 2008). This has resulted in an increased interest in identifying reservoirs of both antimicrobial-resistant strains of enterococci and genes coding for resistance properties (Rice et al, 1995;Kolar et al, 2000;Manson et al, 2004;Olson et al, 2006).…”
mentioning
confidence: 99%
“…Iversen et al (2002) observed that 60% of the residual water samples from four sewage treatment plants in Sweden, 36% of hospital sewage effluent and 19% of those of treated sewage had vancomycin-resistant strains. Similarly, Talebi et al (2007) detected resistance to Van in 19% of Enterococcus strains isolated in three sewage treatment plants in Iran.…”
Section: Discussionmentioning
confidence: 99%